KIBRA gene polymorphism has no association with verbal or visual episodic memory performance - Franks, Katherine H.; Summers, Mathew J.; Vickers, James C. (Frontiers in Aging Neuroscience, 2014)
Inter-individual variability in memory performance has been suggested to result, in part, from genetic differences in the coding of proteins involved in long-term potentiation (LTP). The present study examined the effect of a single-nucleotide polymorphism (SNP) in the KIBRA gene (rs1707045) on episodic memory performance, using multiple measures of verbal and visual episodic memory. A total of 256 female and 130 male healthy, older adults (mean age = 60.86 years) were recruited from the Tasmanian Healthy Brain Project, undergoing both neuropsychological and genetic testing. The current study showed no significant effect of the KIBRA polymorphism on performance on the Rey Auditory Verbal Learning Task, Logical Memory test, Paired Associates Learning test or Rey Complex Figure Task. The results suggest there is little to no functional significance of KIBRA genotype on episodic memory performance, regardless of modality.